Shapiro steps and nonlinear skyrmion Hall angles for dc and ac driven skyrmions on a two-dimensional periodic substrate - Vizarim, N. P. [UNESP]; Reichhardt, C.; Venegas, P. A. [UNESP]; Reichhardt, C. J.O. (American Physical Society (APS), 2020)
For an overdamped particle moving over a two-dimensional periodic substrate under combined dc and ac drives, a series of steps can appear in the velocity force curves that are known as Shapiro steps. Here we show that for skyrmions driven over a two-dimensional periodic obstacle array with a dc drive and an ac drive that is either parallel or perpendicular to the dc drive, the system exhibits numerous transverse and longitudinal synchronization dynamics due to the Magnus force. These phenomena originate in interactions between two different types of phase-locking effects: Shapiro steps and directional locking. In some cases, the skyrmion Hall angle is constant but longitudinal Shapiro steps appear, while in other regimes the skyrmion Hall angle can either increase or decrease with increasing dc drive during the phase locking as the skyrmion locks to different symmetry directions of the obstacle lattice. For a transverse ac drive, we find that strong Hall angle overshoots can occur in certain locked phases where the skyrmion is moving at an angle that is considerably larger than the intrinsic Hall angle. For the strongest Magnus force, the phase-locking effects are reduced and there are larger regions of disordered dynamics. We show that the skyrmion Hall angle can be controlled by fixing the dc drive and changing the amplitude of the ac drive.